Impact of instrumental delivery in theatre on short-term neonatal outcomes: is it time for new standards?. (16th November 2010) - Tower, CL; Caine, N; Vause, S
Abstract : Background: Decision to delivery intervals (DDI) are widely used in obstetric practice to audit emergency Caesarean sections. However, there is limited data available regarding DDI for instrumental deliveries, and there are no recommendations. The authors investigated DDI and short term neonatal outcomes in a large tertiary referral centre in the UK. Methods: The authors investigated instrumental deliveries for 1 year in a tertiary referral centre (October 2008–September 2009). Data were prospectively collected using an audit proforma that also served as medical documentation. Results: The total number of instrumental deliveries was 552 and 221 (40%) were conducted in theatre. Vaginal delivery was achieved in 209/221 (94.5%) of theatre cases. DDI was available for 258 deliveries in the room and 187 deliveries in theatre. The median DDI for deliveries in the room was 13 min (interquartile range, IQR 9–17 min) and for deliveries in theatre was 36 min (IQR 28–52 min), p<0.001, Mann–Whitney U test. This increased DDI was associated with a lower arterial pH of 7.18 (IQR 7.13–7.24) vs 7.21 (IQR 7.16–7.27), p =0.001, Mann–Whitney U test. There was a small, non-significant increase in the number of babies admitted for neonatal care directly from the delivery unit of 13/221 (5.9%) vs 12/331 (3.6%). Conclusion: Babies undergoing instrumental deliveries in theatre take approximately three times longer to deliver than those delivered in the room, and this is associated with an increase in fetal acidosis. The time has come to recommend DDI for instrumental deliveries to provide an auditable standard, with the aim of improving fetal outcomes.